Shocks, Production, Exports and Market Prices: An Analysis of the Rice Sector in Myanmar - Dorosh, Paul; Aung, Nilar (2023)
An output of the Myanmar Strategy Support Program, with USAID and Michigan State University. Presented by Paul Dorosh, Director, Development Strategy and Governance Unit, International Food Policy Research Institute and Nilar Aung, Research Specialist, Michigan State University.